'Virtual museums' as digital collection complexes. A museological perspective using the example of Hans-Gross-Kriminalmuseum. (27th May 2017) - Biedermann, Bernadette
ABSTRACT: The term 'virtual museum' used in German-speaking areas is defined differently in various disciplines such as museology and digital humanities. In the museum context, it usually refers to all digital provisions of museum object data in the web. Digital sceptics worry about the aura and the loss of authenticity of the original object. This paper examines the significance of digital technologies for core museum tasks of collecting, investigating and mediating museum object data from the perspective of museology. It is based on the assumption that presentations of museum objects in a virtual space cannot compete with real museum exhibitions, as they cannot replace an encounter with the original object. Additionally, they serve as a medium in their own right. Virtually represented collection complexes can be used as an independent educational tool by linking multi-layered meanings of museum objects. These presuppositions are demonstrated using the example of a physical museum collection.